Rules of Interpretation of Verses Related to Social Aspects in the Qur’an - Taryudi, Taryudi; Fathurrohman, Asep Ahmad (UIN Sunan Gunung Djati Bandung, 2023)
This article discusses qawā'id al-tafsīr (rules of interpretation) regarding verses relating to social aspects in the Al-Quran. This research aims to find out the ta'qid masalik developed by Muslim scientists in interpreting Al-Quran verses and to present interpretive principles related to social verses in the Al-Quran. This research is based on a literature review using qualitative methods. The primary sources in this research are verses from the Koran relating to social aspects, while secondary sources come from books, scriptures, and articles relevant to the research theme. The results obtained from the research are that the maslak ta'qid developed by Muslim scientists from the classical to contemporary eras were found to be based on istiqrā', istinbāṭ, and al-ta'qid maslak based on texts. And, 20 rules of interpretation can be used as a guide in studying verses related to social aspects.